Development Communication Challenges in Preserving Tambi Coffee Farms and Revitalizing Critical Lands - Laily Furaida (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
Critical land has caused concern among many stakeholders because it can have serious impacts. This has become the main agenda in sustainable development carried out by development actors. One form of revitalization is carried out by improving soil structure by planting coffee which is initiated through collaboration between institutions and involving the local community. The study in this article uses a narrative review. The approach used is done by reviewing each article that develops from time to time and is considered possible and relevant as the basis for analysis. The data analysis used is a simplified approach. The steps taken in the simplified approach analysis are summarizing each piece of literature. Critical appraisal is carried out simultaneously to determine the strengths and weaknesses of the literature and to see the relationship between one literature and another. This study found that development actors consisting of facilitators, mediators, other change agents, and beneficiaries, both between the government and the community or the private sector and the community, have challenges as well as decisive roles in building the face of development from various interest perspectives. Capacity building either through education, training, or improving the communication channels used determines the effectiveness of cooperation in the perspective of development communication that affects the success of development programs.